Drug-Loaded Bioscaffolds for Osteochondral Regeneration - Yifan Tong; Jiaqi Yuan; Zhenguang Li; Cuijun Deng; Yu Cheng (MDPI AG, 2024)
Osteochondral defect is a complex tissue loss disease caused by arthritis, high-energy trauma, and many other reasons. Due to the unique structural characteristics of osteochondral tissue, the repair process is sophisticated and involves the regeneration of both hyaline cartilage and subchondral bone. However, the current clinical treatments often fall short of achieving the desired outcomes. Tissue engineering bioscaffolds, especially those created via three-dimensional (3D) printing, offer promising solutions for osteochondral defects due to their precisely controllable 3D structures. The microstructure of 3D-printed bioscaffolds provides an excellent physical environment for cell adhesion and proliferation, as well as nutrient transport. Traditional 3D-printed bioscaffolds offer mere physical stimulation, while drug-loaded 3D bioscaffolds accelerate the tissue repair process by synergistically combining drug therapy with physical stimulation. In this review, the physiological characteristics of osteochondral tissue and current treatments of osteochondral defect were reviewed. Subsequently, the latest progress in drug-loaded bioscaffolds was discussed and highlighted in terms of classification, characteristics, and applications. The perspectives of scaffold design, drug control release, and biosafety were also discussed. We hope this article will serve as a valuable reference for the design and development of osteochondral regenerative bioscaffolds and pave the way for the use of drug-loaded bioscaffolds in clinical therapy.